The Relationship Between the Recognition of Basic Emotions and Negative Symptoms in Individuals With Schizophrenia Spectrum Disorders – An Exploratory Study - Zierhut, Marco; Böge, Kerem; Bergmann, Niklas; Hahne, Inge; Braun, Alice; Kraft, Julia; Ta, Thi Minh Tam; Ripke, Stephan; Bajbouj, Malek; Hahn, Eric (Frontiers in Psychiatry, 2022)
Current research suggests that emotion recognition is impaired in individuals affected by schizophrenia spectrum disorders (SSD). However, the specific impact of negative symptoms on the ability to recognize single basic emotions has not yet been explored sufficiently and is the aim of the present study. A sample of N = 66 individuals diagnosed with SSD was recruited at the Charité – Universitätsmedizin Berlin. In a first step, correlation analyses were conducted between seven different negative symptom subdomains of the Positive and Negative Syndrome Scale (PANSS) and the accuracy and latency in recognizing the six basic emotions (anger, disgust, fear, happiness, sadness, surprise) using the Emotion Recognition Task (ERT) of the Cambridge Neuropsychological Test Automated Battery (CANTAB). The significant correlations were subjected to linear regression models that controlled for the significant covariates diagnoses, age, sex, and education. Results revealed that in individuals with SSD the negative symptom domain of blunted affect significantly predicted the accuracy of emotion recognition performance (p < 0.05), particularly, when recognizing happiness (p < 0.05). Additionally, we found that stereotyped thinking also predicted the performance of emotion recognition, especially the response latency (p < 0.05) and difficulty in abstract thinking predicted the recognition of fear (p < 0.05). However, the nominal significances did not withstand correction for multiple tests and therefore need to be followed up in further studies with a larger sample.